COVID-19 Vaccine Safety in Adults: A Narrative Review of Adverse Reactions in ASEAN Countries - Andini, Prasti; Darmawan, Endang; Muflih, Anhar; Ridwan, Muhammad (Scripta Medica, 2026)
The spread of the SARS-CoV-2 virus, known as the COVID-19 virus, which causes the coronavirus disease 2019 known as “COVID-19”, has led to a rapid response from governments around the world. In response to the significant threat it presents to global health, comprehensive strategies have been implemented to mitigate worldwide transmission and reduce mortality rate. Association of South East Asian Nations (ASEAN) countries have also taken steps to encourage people to get vaccinated. The use of vaccines from many global pharmaceutical companies has led to the collection of reports on adverse drug reactions to monitor and evaluate the use of pharmaceutical products after administrated. This study aimed to evaluate the adverse drug reactions of COVID-19 vaccines administered in ASEAN countries through a narrative review of relevant scientific literature. A narrative review was conducted using PubMed and ScienceDirect databases to identify original, open-access studies published between 2020 and 2025. Eligible articles involved adults aged 18–59 years and reported adverse events following COVID-19 vaccination in ASEAN countries. Nine studies met the inclusion criteria and were qualitatively analysed. Six vaccines were evaluated: Ad26.COV2.S (Johnson &Johnson), AZD1222 (AstraZeneca), BNT162b2 (Pfizer-BioNTech), CoronaVac (Sinovac), Sputnik V and mRNA-1273 (Moderna). The most adverse drug reactions reported included injection site pain, fever, headache, fatigue and muscle pain, respectively, based on the severity of side effects. Current evidence confirms that COVID-19 vaccines used in Southeast Asian demonstrated favourable safety and tolerability profiles among adults, consistent with global pharmacovigilance data. These findings support continued vaccination programs and highlight the importance of strengthening regional pharmacovigilance systems and harmonised AEFI reporting to sustain public confidence in immunisation efforts across ASEAN.
Keywords: Adverse drug reactions; COVID-19 vaccines; Pharmacovigilance; Southeast Asian